Feeding Guild of Birds in Rojolelo Forest Park (TAHURA) Central Bengkulu - Susanto, Eki; Riandini, Evelyne; Rivai, Muhammad Prima Putra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The composition of bird guilds can provide an overview of the vertical distribution of birds. Rojolelo Forest Park (TAHURA) is a green area that plays a role in maintaining the ecosystem balance for living beings, especially birds. This research aims to determine the composition of bird guilds in Rojolelo Forest Park (TAHURA). The research was conducted in June-July 2023 at several locations, they are TAHURA Lodge, scrubland, and irrigation areas. Data collection was conducted using point counts method. The research results obtained 21 families, 33 species of birds, and were grouped into 7 types of guilds. The seven types of guilds are insectivores, nectarivores, granivores, omnivores, piscivores, carnivores, and frugivores. The insectivores dominated in guild composition with 17 species.